Enhanced efficiency in dye-sensitized solar cell based on zinc oxide-modified poly(ethylene oxide) gel electrolyte - Chan, X.H.; Khanmirzaei, Mohammad Hassan; Omar, Fatin Saiha; Ramesh, Kasi; Ramesh, Subramaniam; Ramesh, Singh (Springer Verlag (Germany), 2018)
Gel polymer electrolytes (GPEs) are more preferable than liquid electrolyte for dye-sensitized solar cells (DSSCs) due to several advantages. However, GPEs have poor ionic conductivity which renders the low efficiency of DSSCs. GPE systems based on poly(ethylene oxide) (PEO) as host polymer, sodium iodide (NaI) salt, and various amount of zinc oxide (ZnO) (1, 3, 5, and 7 wt%) were prepared and optimized. The highest ionic conductivity obtained for these systems was 7.05 × 10−3 S cm−1 for the GPE at 5 wt% of ZnO. The formation of structural features and complexes of the materials have been confirmed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). Under the illumination of AM 1.5 (100 mW cm−2), the fabricated DSSCs (with an arrangement of FTO glass/TiO2/N719dye/electrolyte/Pt/FTO glass) achieved the maximum power conversion efficiency of 6.94%, with a maximum short-circuit current density (JSC) of 18.75 mA cm−2, open-circuit voltage (VOC) of 0.666 mV, and fill factor (FF) of 55.6%.